Nonlinear Mathematical Model of Contaminant Distribution in Unsaturated Catalytic Porous Media - Zhukovskyy, Viktor; Vlasyuk, Anatolyy; Zhukovska, Natalya; Hesham, Rajab (Моделювання, керування та інформаційні технології, 2019)
The nonlinear mathematical model of contaminant distribution in unsaturated catalytic porous media to the filter-trap in isothermal conditions is presented. The mathematical model takes into account the micro and the meso/macro scale factors of the heat and mass transfer processes. The numerical solution of the respective boundary value problem was obtained by the method of finite differences. The analytical solution for mass transfer in nanoparticles was presented as well.